Consumer attitudes towards luxury fashion apparel made in sweatshops. Issue 2 (11th May 2015) - Phau, Ian; Teah, Min; Chuah, Joe
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine how attitudes towards sweatshops, social norms and perceived behavioural control (PBC) factors influence consumers' attitudes towards luxury fashion apparel made in sweatshops. It also examines how these variables influence purchase intention and ultimately the willingness to pay more for luxury fashion apparel not made in sweatshops. Design/methodology/approach – A self-administered questionnaire was designed using established scales. A survey was conducted through the "mall intercept" method. Findings – Underpinned by the theory of planned behaviour (TPB) model, attitudes and PBC were found to have an influence on intention to purchase luxury fashion apparel made in sweatshops. The intention to purchase luxury fashion apparel also significantly influences the willingness to pay more for luxury fashion apparel not made in sweatshops. Practical implications – The research findings can be used to formulate strategies for academia, practitioners and, more importantly, policy makers to help curb sweatshop activities. Originality/value – This paper focuses exclusively on luxury fashion apparels made in sweatshops. Status consumption is also added as a potential antecedent towards purchase intention.